KEBUDAYAAN SIMBOLIK; Etnografi Religi Victor Turner - Santri Sahar (SOSIORELIGIUS, 2019)
This Artical presents a cultural study of Victor Turner's symbolic anthropological perspective, obtained through Turner's primary sources. Starting Ritual from Turner's scientific background, his works until he sparked an influential symbolic theory and became a tradition of social anthropological studies in England. This concept was adapted from Van Gennep's theory of life cycle ceremonies, Turner formulated the phases of human life into separation, liminality and regregation. Through the mudyi tree as a symbol in ritual, the Ndembu people identify their identity which is always dialectic between the community and community through liminality. Keywords: Turner, Culture, Symbolic, Ritual AbstrakTulisan ini menyajikan kajian budaya perspektif antropologi simbolik Viktor Turner, yang diperoleh melalui sumber primer karangan Turner . Dimulai dari latar belakang keilmuan Turner, karya-karyanya hingga ia mencetuskan teori simbolik yang berpengaruh dan menjadi tradisi kajian antroplogi sosial di Inggris. Konsep Ritual  ini diadaptasi dari teori Van Gennep tentang upacara siklus hidup, Turner merumuskan fase kehidupan manusia menjadi separasi, liminalitas dan regregasi. Melalui pohon mudyi sebagai simbol dalam ritual, orang Ndembu mengidentifikasi identitas diri yang selalu berdialektika antara masyarakat dan komonitas melalui liminalitas.